Can my library help with Europeana?: the need for a change in perceptions - Juárez-Urquijo, Fernando (Anuario ThinkEPI, 2013)
The Spanish city of Burgos hosted the VI National congress of public libraries and the Europeana conference, October 9-11, 2012. The events shared venues and registrants under the theme of "Public library: individual memory, global heritage". Building the European memory requires the involvement of citizens and Europeana is working hard to achieve it. The difficulties encountered by public libraries attempting to become involved in the project are described, pointing out some of the things they can do to integrate local memory into the larger repositories.
Keywords: Public library; Europeana; Local memory.